2010
DOI: 10.1128/jvi.01663-09
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of D212 from Sulfolobus Spindle-Shaped Virus Ragged Hills Reveals a New Member of the PD-(D/E)XK Nuclease Superfamily

Abstract: Structural studies have made significant contributions to our understanding of Sulfolobus spindle-shaped viruses (Fuselloviridae), an important model system for archaeal viruses. Continuing these efforts, we report the structure of D212 from Sulfolobus spindle-shaped virus Ragged Hills. The overall fold and conservation of active site residues place D212 in the PD-(D/E)XK nuclease superfamily. The greatest structural similarity is found to the archaeal Holliday junction cleavage enzymes, strongly suggesting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 59 publications
(77 reference statements)
0
24
0
Order By: Relevance
“…The X-ray structure of the D244 orthologue from the Sulfolobus spindle-shaped virus Ragged Hills revealed that the protein is a member of the PD-(D/E)XK nuclease superfamily (84), arguing against the possibility that D244 plays a structural role in virion formation. We could not detect D244 in our virus preparation, although its presence in amounts that were below our detection limit cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray structure of the D244 orthologue from the Sulfolobus spindle-shaped virus Ragged Hills revealed that the protein is a member of the PD-(D/E)XK nuclease superfamily (84), arguing against the possibility that D244 plays a structural role in virion formation. We could not detect D244 in our virus preparation, although its presence in amounts that were below our detection limit cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…A second reason to suspect insertion into telomeres is that the predicted MoTeR1 RT protein shares amino acid residues found in the RELendo domains of RTs encoded by site-specific retroelements that recognize and cleave their genomic targets. The MoTeRs encode proteins with a slight variant of the PD-(D/E) motif, namely AD-D, which happens to be present in the HincII restriction enzyme (Menon et al 2010) and several newly identified type II endonucleases (Kosinski et al 2005). The presence of a REL-endo domain suggests that MoTeR insertion also initiates through the recognition and cleavage of a specific sequence-in this case, telomere repeats.…”
Section: Discussionmentioning
confidence: 99%
“…The only nonessential core gene was vp3, which is surprising considering its high degree of conservation and presence as a minor structural protein within the virion (17,18,20). Because the VP3 and proteolytically processed VP1 proteins are highly similar (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…SSV1-B251 possesses NTP binding motifs and is predicted to be homologous to the bacterial dnaA gene (28). The structure of SSV8-D212, a homologue of SSV1-D244, has a predicted nuclease fold, although activity was not demonstrated biochemically (20). SSV1-D244 was identified in one study by mass spectrometry of purified SSV1 virions, but it was not detected in a later analysis (18,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation